WHAT DO PATIENTS WITH ATRIAL FIBRILLATION KNOW ABOUT STROKE AND SYSTEMIC EMBOLISM PREVENTION? DATA OF THE PRIMA-TERRA REGISTRY - R. М. Linchak; O. G. Kompaniyets; A. M. Nedbaykin (Рациональная фармакотерапия в кардиологии, 2018)
Aim. To study the awareness and opinion of patients with atrial fibrillation (AF) about the stroke prevention.Material and methods. This study based on the questionnaire survey of 544 patients from three regions of Russia is the third part of the PRIMA-TERRA register. The survey was carried out in the period from 01.12.2012 to 01.07.2013 by independent employees on a special questionnaire of 9 questions. The ratio of men and women was 42% vs 58%, respectively, the average age was 65.6Ѓ}8.2 years. The AF duration was 7.6Ѓ}2.0 years. The average score of CHA2DS2-VASc was 3.4Ѓ}1.4.Results. Less than 70% of patients were informed of possible AF complications, of which less than a third – about the risk of stroke. Only 62% of patients believed that they take drugs for the stroke prevention, of which only 31% took warfarin, 15% new oral anticoagulants (NOAC). The majority of patients received antiplatelet agents and their combinations – medications not recommended for this purpose by modern National and European cardiology guidelines. Less than 60% of the respondents were informed about the NOACs, while clinically significant information about the benefits of this group of drugs was provided by doctors only to 18% of patients. The main reason limiting the widespread use of NOACs is the high cost of these drugs.Conclusion. Awareness of patients about AF thromboembolic complications is extremely inadequate. For the prevention of stroke, most patients take antiplatelet agents and their combinations, less than a half – anticoagulants. The main reason for refusing to receive the NOACs is the high cost of this group of drugs.